Interpersonal Communication Skills Training for Kader Surabaya Hebat (KSH) in Sukolilo Village - Nurahaju, Rini; Nurcholis, Gartinia; Widanti, Nurul Sri; Untari, Dwi Warih (Society : Jurnal Pengabdian Masyarakat, 2025)
According to data from Sukolilo District, the Kader Surabaya Hebat have 20 members. Their role is to assist residents and families in implementing Clean and Healthy Lifestyles (PHBS). However, in carrying out their duties, problems often arise, ranging from ridicule, accusations of manipulating and exploiting residents' data for personal gain, to the spread of conspiracy theories and hoaxes. These problems hamper the Surabaya City Government's PHBS program, especially when it is not supported by effective communication between cadres and the community. Therefore, the Faculty of Psychology at the University of North Sumatra (UHT) conducted an empowerment intervention to improve interpersonal communication in Sukolilo Village. This one-day activity included counseling and a Q&A session with 15 female cadres. The activity was measured using a Likert-based effective communication questionnaire to gauge understanding before and after the training. The questionnaire was based on indicators of openness, empathy, support, positive attitudes, and equality. This activity was attended by 15 female cadres. The results showed no significant difference before and after the training. Recommendations include conducting regular mentoring activities and ensuring improvement by practicing effective interpersonal communication skills.